The precedence of syntax in the rapid emergence of human language in evolution as defined by the integration hypothesis - Nóbrega, Vitor A.; Miyagawa, Shigeru (Frontiers in Psychology, 2015)
Our core hypothesis is that the emergence of human language arose very rapidly from the linking of two pre-adapted systems found elsewhere in the animal world—an expression system, found, for example, in birdsong, and a lexical system, suggestively found in non-human primate calls (Miyagawa et al., 2013, 2014). We challenge the view that language has undergone a series of gradual changes—or a single preliminary protolinguistic stage—before achieving its full character. We argue that a full-fledged combinatorial operation Merge triggered the integration of these two pre-adapted systems, giving rise to a fully developed language. This goes against the gradualist view that there existed a structureless, protolinguistic stage, in which a rudimentary proto-Merge operation generated internally flat words. It is argued that compounds in present-day language are a fossilized form of this prior stage, a point which we will question.